"An Eleven-Year-Old Controversy": Comment to Starn's article - Salomon, Frank (1992)
Starn wields an eleven-year-old polemic, and in doing so recalls a significant passage in intellectual history. How successfully has he problematized the approach of "the anthropologists" (by which he means those graduates in the United States) regarding the Andes during the 1970s and 1980s? He has established enough analytical distance to practice the producers, but not enough to problematize them in their own contexts.